In silico evaluation of phenolic compounds as inhibitors of Α-amylase and Α-glucosidase. Issue 3 (11th February 2021) - Abdelli, Imane; Benariba, Nabila; Adjdir, Sara; Fekhikher, Zohra; Daoud, Ismail; Terki, Mohammed; Benramdane, Hanane; Ghalem, Said
Abstract: The aim of the present study focuses on the molecular docking approach to screen alternative drug that can regulate the hyperglycemia by down-regulating α-glucosidase and α-amylase activity using phenolic compounds: tannic acid (L1), catechin (L2), gallic acid (L3), quercetin (L5) and epicatechin (L6). L1 gives the best docking scores, its interaction with α-amylase and α-glucosidase has the lowest energy score compared to the other complexes and to the acarbose (L4). L1 forms strong five H-donor interactions with residues of active site of α-amylase and three H-donor interactions with α-glucosidase. The in silico evaluation of the unfavorable absorption, distribution, metabolism, and elimination (ADME) properties and drug-likeness revealed that L5 has high absorption compared to tannic acid and to the other compounds. This study revealed for the first time that tannic acid is a functional inhibitor of α-glucosidase and α-amylase activities and can be used as alternative for the regulation of post-prandial hyperglycaemia. Communicated by Ramaswamy Sarma